Leo Strauss on democracy, technology, and liberal education - Burns, Timothy, 1958- (Albany : State University of New York Press, 2021)
Liberal democracy is today under unprecedented attack from both the left and the right. Offering a fresh and penetrating examination of how Leo Strauss understood the emergence of liberal democracy and what is necessary to sustain and elevate it, Leo Strauss on Democracy, Technology, and Liberal Education explores Strauss' view of the intimate (and troubling) relation between the philosophic promotion of liberal democracy and the turn to the modern scientific-technological project of the "conquest of nature." Timothy W. Burns explicates the political reasoning behind Strauss' recommendation of reminders of genuine political greatness within democracy over and against the failure of nihilistic youth to recognize it. Elucidating what Strauss envisaged by a liberally-educated sub-political or cultural-level aristocracy--one that could elevate and sustain liberal democracy--and the roles that both philosophy and divine-law traditions should have in that education, Burns also lays out Strauss' frequent (though often tacit) engagement with the thought of Heidegger on these issues.
Intro -- Contents -- Acknowledgments -- Introduction -- Modern Political Thought as Technological Thought -- Technology and Democracy -- Chapter One Democracy and Liberal Education -- Contemporary Nihilists, Ancestral Traditions, and Liberal Education -- Chapter Two An Aristocracy within a Democracy: "Liberal Education and Responsibility" -- The Rise of Modern Science and the Evolution to Modern Democracy -- Chapter Three "German Nihilism" -- The Place of the Old Moral Reasoning -- Moral Reasoning and Ancestral Traditions -- Tradition and the Health of Liberal Democracy -- Chapter Four "The Liberalism of Classical Political Philosophy" -- Havelock's Liberalism -- Disinterring Greek Liberalism: Aeschylus and Sophocles -- Reconstructing the Anthropologists' Teaching: Protagoras and Republic -- The Account of the Fragments of Antiphon -- Chapter Five Concluding Reflections on Moral-Political Reasoning in Contemporary Liberal Democracy -- Index.
Includes bibliographical references and index.
JSTOR
Keywords: Strauss, Leo; Strauss, Leo; Democracy; Liberalism; Education, Humanistic; Political science -- Philosophy; Free enterprise; Libéralisme.; Éducation humaniste; liberalism; PHILOSOPHY / Political; Free enterprise; Democracy; Education, Humanistic; Liberalism; Political science -- Philosophy